THE ROLE OF LANGUAGE SKILLS IN ENHANCING WORKFORCE COMPETITIVENESS AND PRODUCTIVITY - Sultanova Shohistaxon Shavkatovna (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: This paper explores the critical role of language skills in enhancing workforce competitiveness and productivity in an increasingly globalized economy. It examines how proficiency in multiple languages contributes to effective communication, cross-cultural collaboration, and access to broader markets. The study also analyzes the correlation between language skills and employability, wage premiums, innovation capacity, and business efficiency. Drawing on examples from multilingual economies, multinational companies, and global trade contexts, the paper highlights how language competence can serve as a strategic economic asset for both individuals and organizations. Furthermore, it emphasizes the importance of integrating language training into educational curricula and professional development programs to prepare a globally competitive workforce.